Modelo de gestión para el aprovisionamiento de alimentos kilómetro cero en restaurantes de segunda categoría de Portoviejo, provincia de Manabí - Párraga Andrade, Miriam Jessenia (2021)
The present study had as its objective to design a management model for the supply of food kilometer zero in second category restaurants in Portoviejo. This investigation is of qualitative type with an explorative-descriptive focus. The development of the research consisted of three phases, in the first phase, a diagnosis of the area of study was carried out for the identification of the typology of the restaurants, this was done by means of bibliographical review and field visits; for the analysis of the demand and suppliers, interviews and surveys were applied, afterwards a strategic analysis was carried out through the SWOT matrix. In the second phase the management of supply was evaluated and a system of twenty-six indicators was established. Through this means it was determined that the highest scores were the selection and analysis of the suppliers considering that they are demanding on this aspect. Concerning the purchases request, the lowest scores were found due to the limited existence of means by which they place orders and make payments. Finally, it is proposed the management model composed by two macro strategies with the intention of reformulating the external and internal management of supply, offering new products and choosing suppliers kilometer zero.